2014
DOI: 10.1186/s12884-014-0419-6
|View full text |Cite|
|
Sign up to set email alerts
|

Unsafe abortion in rural Tanzania – the use of traditional medicine from a patient and a provider perspective

Abstract: BackgroundThe circumstances under which women obtain unsafe abortion vary and depend on the traditional methods known and the type of providers present. In rural Tanzania women often resort to traditional providers who use plant species as abortion remedies. Little is known about how these plants are used and their potential effect.MethodsData were obtained among women admitted with incomplete abortion at Kagera Regional Hospital during the period January - June, 2006. The women underwent an empathetic intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 23 publications
1
41
0
2
Order By: Relevance
“…In addition, little is known about the methods that women currently use to try to terminate their own pregnancies and that contribute to abortion-related morbidity; a 2006 study in nearby Tanzania reported that the most common method used there were plants believed to cause uterine contractions. 38 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, little is known about the methods that women currently use to try to terminate their own pregnancies and that contribute to abortion-related morbidity; a 2006 study in nearby Tanzania reported that the most common method used there were plants believed to cause uterine contractions. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, access to safe, legal abortion must now be seen as a fundamental right of women, irrespective of where they live. Moreover, making abortion legal, safe, and accessible does not appreciably increase demand as shown by some studies 4,5,22 . Instead, the principal effect is shifting previously clandestine, unsafe procedures to legal and safe ones 27 .…”
Section: Discussionmentioning
confidence: 99%
“…'Unsafe abortion' is defined as a procedure for terminating a pregnancy carried out either by persons lacking the necessary skills or in an environment that does not conform to minimal medical standards, or both 2 . Although the overall global abortion rate has declined, the proportion of unsafe abortion is on the rise, especially in low-income countries where 55% of abortions are unsafe compared to only 3% in high-income countries 1,3,4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…In all these studies, women most often chewed or consumed herbs as a strong tea. On the contrary, ndings in a related study in a referral hospital in rural north-western Tanzania revealed that less than a fth of women reported using herbs orally [25]. However, that study looked at only women who used herbs for inducing abortion.…”
Section: Discussionmentioning
confidence: 93%